2016
DOI: 10.1155/2016/5460241
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Reactive Powder Concrete and Its Application in Highway Bridge

Abstract: A high-performance reactive powder concrete (RPC) was prepared with river sand, and the maximum particle size is 1.25 mm, under the 80°C steam curing condition. It is tested completely in terms of strength, uniaxial compressive stress-strain relation, flexural load-deflection relation, and frost resisting durability, and the results indicate that the concrete is suitable to RPC200. The uniaxial compressive stress-strain curve shows a linear-elastic behaviour up to explosive failure, which is different from tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…It was detected that the constitutive relationship of RPC is similar to that of mortar which is typical elastic brittle material [3]. The last mentioned research also indicated that the compressive stress-strain relation of the RPC has a linear ascending stage until the ultimate strain is reached.…”
Section: Introductionmentioning
confidence: 83%
“…It was detected that the constitutive relationship of RPC is similar to that of mortar which is typical elastic brittle material [3]. The last mentioned research also indicated that the compressive stress-strain relation of the RPC has a linear ascending stage until the ultimate strain is reached.…”
Section: Introductionmentioning
confidence: 83%
“…Compared with conventional concrete, the advantages of RPC were as follows. (1) Super high strength [3]: the weight of RPC structure dramatically reduced compared with the corresponding conventional concrete structures at the same loading condition [4]. This characteristic expanded the application range of RPC in high-rise buildings and largespan structures.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, RPC had high resistance to deicing salts, freeze-thaw cycles, and aggressive environments. (3) High performance of impact behavior [6]: former research had been showing that the antipenetration performance of RPC was up to 3 times of C30 concrete [7], which made it have a broad application prospect in protective engineering and antiearthquake engineering. (4) Self-healing ability: the water-binder ratio of RPC materials was very low generally between 0.17 and 0.22, so there was a significant amount of unhydrated cement in finished products which might provide a self-healing potential after the generation of crack [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although many researchers around the world have investigated the properties of RPC, including mixture proportion, mechanical characteristics, and durability, a wide implementation of RPC as a construction material into construction business is limited because of its relatively high cost of production [21,22]. The addition of expensive steel fibers and the special treatment of a curing regimen influence the overall cost of RPC [8].…”
Section: Introductionmentioning
confidence: 99%